Hubungan Unsafe Action Penggunaan Gadget Dengan Nilai Visus Pada Remaja Miopia Di Rumah Sakit Daerah Balung Kabupaten Jember - Siswoyo Siswoyo; Muhamad Zulfatul A’la; Linda Novema; Kushariyadi Kushariyadi (Bima Nursing Journal, 2022)
Introduction: Myopia is a type of refractive disorder that has a high prevalence in the world and happens on teenagers. Myopia is caused by bad habits when looking at an object, one of them is the habit when using a gadget. Method: Research design used is observational analytics. The sampling technique used was consecutive sampling and obtained 84 teenagers aged 15-24 years with myopia. The data obtaining used was unsafe action questionnaires of gadgets use and vision inspection sheets. Result: The results showed that the median unsafe action of gadget use is 26.5 with a minimum score is 16 and a maximum is 32. The median of vision value is 0.25 with a minimum value is 0.03 and a maximum is 0.83. Analysis: The results of this research indicate that there is a relationship between unsafe action of gadgets use and visual value on teenagers with myopia (p value = <0.001; r = 0.474). Conclusion: Teenagers pay less attention to position, visibility, duration of use, and lighting when using a gadget. Using a gadget with a sitting position, a minimum visibility is 30 cm and a maximum usage time is 2 hours with a rest of 20 minutes can prevent eye strain. In addition, increasing nutritional needs and exercising can prevent a decrease in visual acuity.